Techniques and cuff pressure management in patients with an artificial airway performed by Speech and Language Therapists in Chile - Rosales Lillo, Felipe Gonzalo; Monichi Valdenegro, Giovanna; Miranda Llanos, Francisca; Marín Garrido, Fabiola (Revista de Investigación en Logopedia, 2022)
A descriptive, observational and transversal study which aimed to describe the cuff pressure management and the techniques performed by Speech and Language Therapists in Chile in adult patients with an artificial airway. The population was Speech and Language Therapists with experience attending adult patients with an artificial airway in Chile, and a convenience sampling. An online questionnaire on the techniques and cuff pressure management in artificial airway patients performed by health professionals in Chile was employed which had numerical and categorical variables. Descriptive and analytical analyses were performed. The study was approved by the Ethic Research Committee from ‘Universidad del Desarrollo’. 98% of the participants use objective technique and 46% subjective methods. The subjective digital-palpation technique is the most used by the clinicians. 54% of the participants use more than one technique during the attention of patients with an artificial airway. The median of the minimum and maximum cuff pressure used by the participants is a 25 and 32 centimetres of water. There was a significant difference between the minimum cuff pressure used by participants from public high-complex hospitals versus those from private hospitals. In conclusion, the minimum and the maximum cuff-pressure values reported by the participants in Chile could be unsafe during the attention of adult patients with an artificial airway, especially with the use of subjective techniques. The use of current references is suggested, along with an update of institutional protocols, the development of a national guideline and the encouragement of colleagues in other countries to review their protocols.